ENHANCING ARABIC LANGUAGE PROFICIENCY THROUGH INTERACTIVE DIGITAL LEARNING PLATFORMS: A QUASI-EXPERIMENTAL STUDY IN HIGHER EDUCATION - Ahmad Maghfurin; Ramdhan Yurianto; Hasyim Asy’ari; Silviatul Hasanah (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
The integration of digital technology has increasingly transformed language learning practices in higher education. However, empirical evidence regarding the effectiveness of interactive learning platforms in Arabic language instruction remains limited. This study aimed to examine the impact of an interactive digital learning platform on university students’ Arabic language proficiency. The research employed a quasi-experimental design using a one-group pre-test–post-test approach. A total of 40 undergraduate students enrolled in an Arabic language course at UIN Saifuddin Zuhri, Purwokerto participated in the study. Students’ language proficiency was measured through standardized tests assessing four language skills: reading, listening, writing, and speaking. The data were analyzed using descriptive statistics, paired sample t-test, and effect size (Cohen’s d). The findings revealed a significant improvement in students’ Arabic language proficiency after the implementation of the interactive learning platform. The average scores increased across all four language skills, with the most substantial improvement observed in speaking ability. Statistical analysis indicated that the difference between pre-test and post-test scores was statistically significant (p < 0.01). Furthermore, the calculated effect sizes ranged from 1.18 to 1.56, indicating a strong practical impact of the learning intervention. These findings suggest that interactive digital platforms can effectively enhance students’ engagement and language learning outcomes. The study highlights the pedagogical potential of integrating Computer-Assisted Language Learning (CALL) and Mobile-Assisted Language Learning (MALL) approaches into Arabic language instruction. The results provide important insights for educators and institutions seeking to improve the effectiveness of Arabic language learning in higher education.